Two‑year clinical performance of indirect restorations fabricated from CAD/CAM nano hybrid composite versus lithium disilicate in mutilated vital teeth. A randomized controlled trial - Haneen Ahmad Shafik Elmoselhy; Olfat EL Sayed Hassanien; Mohamed Fouad Haridy; Maha Abd El Salam El Baz; Shehabeldin Saber (BMC, 2024)
Abstract Trial design This is a randomized, controlled, superiority, double-blinded, parallel-group, two-arms trial with an allocation ratio of 1:1. The aim of this trial was to compare the two-year clinical performance of partial indirect restorations fabricated from CAD/CAM nano-hybrid composite and ceramic lithium disilicate blocks using the modified USPHS criteria. Methods In two parallel groups (n = 50 restorations), fifty participants having mutilated vital teeth with a minimum of two remaining walls were randomly enrolled in this trial and received indirect restorations of either nano-hybrid composite resin blocks (Brilliant, Coltene, Switzerland) or Lithium Disilicate (IPS Emax CAD). The restorations were assessed using modified USPHS criteria by two independent blinded assessors at baseline, six months, one-year and two years follow-up visits. Categorical and ordinal data were presented as frequencies and percentages. Categorical data were analyzed using the chi-square test. Ordinal data were analyzed using the Mann-Whitney U test for intergroup comparisons and Freidman's test followed by the Nemenyi post hoc test for intragroup comparisons. Numerical data were presented as mean and standard deviation values. They were analyzed for normality using the Shapiro-Wilk test. Data were found to be normally distributed and were analyzed using the independent t-test. The significance level was set at p ≤ 0.05 within all tests. Results Forty-eight participants received the allocated intervention and completed the follow-up periods. There was a statistically significant difference between both tested materials for all USPHS criteria regarding Marginal integrity and Marginal discoloration at six-months Follow-up, but with no statistically significant difference at one- and two-year follow-up. Conclusions Both materials showed an acceptable, successful clinical performance along the two-years follow-up period. Clinical relevance The CAD/CAM nano-hybrid composite blocks are as reliable as Lithium disilicate for restoring mutilated vital teeth.